1994
DOI: 10.1002/j.1460-2075.1994.tb06803.x
|View full text |Cite
|
Sign up to set email alerts
|

A novel oncogene, ost, encodes a guanine nucleotide exchange factor that potentially links Rho and Rac signaling pathways.

Abstract: Transfection of NIH3T3 cells with an osteosarcoma expression cDNA library led to the appearance of foci of morphologically transformed cells which were found to harbor a novel oncogene, ost. The ost product was activated by truncation of the N‐terminal domain of the ost proto‐oncogene and was highly tumorigenic in nude mouse assays. The proto‐ost cDNA, isolated subsequently, encodes a predicted protein of 100 kDa containing DH (Db1 homology) and PH (pleckstrin homology) domains. Ost is mainly phosphorylated on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
177
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(190 citation statements)
references
References 39 publications
13
177
0
Order By: Relevance
“…Furthermore, since Lbc is reported to be an exchange factor for RhoA (Zheng et al, 1995), Brx may be expected to function as a Rho-GEF (see below). Thus, Brx represents a novel member of the Dbl family of oncoproteins (reviewed in: Cerione and Zheng, 1996) which includes: Cdc24 and Bcr (Ron et al, 1991), Vav (Adams et al, 1992;Galland et al, 1992), Ect2 (Miki et al, 1993), Ras GRF (Shou et al, 1992), Abr (Heisterkamp et al, 1993), Tim (Chan et al, 1994), FGD1 (Pasteris et al, 1994), Lbc (Toksoz and Williams, 1994), Ost (Horii et al, 1994), Tiam-1 (Habets et al, 1994), Dbs (Whitehead et al, 1995a), Lfc (Whitehead et al, 1995b) and Lsc . The Dbl oncogene was isolated using a transfection focus assay system with DNA from a patient with di use human B cell lymphoma (Eva and Aaronson, 1985), and subsequent studies have revealed the dbl oncogene and proto-dbl oncogene (Ron et al, 1988(Ron et al, , 1991 to regulate cell growth and other diverse cellular functions (Cerione and Zheng, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, since Lbc is reported to be an exchange factor for RhoA (Zheng et al, 1995), Brx may be expected to function as a Rho-GEF (see below). Thus, Brx represents a novel member of the Dbl family of oncoproteins (reviewed in: Cerione and Zheng, 1996) which includes: Cdc24 and Bcr (Ron et al, 1991), Vav (Adams et al, 1992;Galland et al, 1992), Ect2 (Miki et al, 1993), Ras GRF (Shou et al, 1992), Abr (Heisterkamp et al, 1993), Tim (Chan et al, 1994), FGD1 (Pasteris et al, 1994), Lbc (Toksoz and Williams, 1994), Ost (Horii et al, 1994), Tiam-1 (Habets et al, 1994), Dbs (Whitehead et al, 1995a), Lfc (Whitehead et al, 1995b) and Lsc . The Dbl oncogene was isolated using a transfection focus assay system with DNA from a patient with di use human B cell lymphoma (Eva and Aaronson, 1985), and subsequent studies have revealed the dbl oncogene and proto-dbl oncogene (Ron et al, 1988(Ron et al, , 1991 to regulate cell growth and other diverse cellular functions (Cerione and Zheng, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The dbl proteins are themselves oncogenic, stimulate JNK activation and many show exchange factor activity towards the racrelated GTPases (Hart et al, 1994;Horii et al, 1994;Cerione and Zheng, 1996;Denhardt, 1996). Candidate molecules which could act upstream of these exchange factors include the src-like non-receptor tyrosine kinases, Pyk2 and the adaptor molecule shc (Dikic et al, 1996;Chen et al, 1996).…”
Section: Alpha1bmentioning
confidence: 99%
“…The ras proteins regulate a wide variety of cellular processes including growth and di erentiation, and constitutively activated ras is oncogenic. The rac proteins control cytoskeletal assembly (Tapon and Hall, 1997) and the exchange factors that activate rac are also oncogenic (Hart et al, 1994;Horii et al, 1994;Cerione and Zheng 1996) implying that like ras, rac also regulates mitogenic signaling pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Dbs is an exchange factor which activates RhoA and CDC42, with weaker activation of RhoG [25][26][27]. Its rat ortholog is known as Ost [28,29]. Dbs is negatively regulated by an auto-repressive N-terminal region [25,28,29] analogous to the mode of auto-regulation of the related guanine nucleotide exchange factor (GEF), Dbl [30].…”
Section: Introductionmentioning
confidence: 99%
“…Its rat ortholog is known as Ost [28,29]. Dbs is negatively regulated by an auto-repressive N-terminal region [25,28,29] analogous to the mode of auto-regulation of the related guanine nucleotide exchange factor (GEF), Dbl [30]. The natural mechanism of activation of Dbs is unknown, but apparently involves positive regulation of the catalytic GEF domain by phosphoinositide lipids binding to the adjacent PH domain [31,32].…”
Section: Introductionmentioning
confidence: 99%